Norms as a solution to the tragedy of the commons: A co-evolutionary model - Fabian Mankat (Philipps-University Marburg, School of Business and Economics, 2024)
This paper examines how societies can conserve common-pool resources (CPRs) through the cultural transmission of norms. To this end, we introduce an evolutionary model that endogenizes the formation of personal, social, and descriptive norms, thereby unifying existing economic theories on norm evolution. By studying this model in a binary CPR game, we also account for the dynamics of the resource stock and its interplay with norms and behavior. We find that the resource can persist through (1) asymptotically stable equilibrium points where moral perceptions and behavioral routines are either homogeneous or heterogeneous across individuals and (2) an asymptotically stable limit cycle in which moral perceptions remain constant, but herding causes alternating aggregate behavior and fluctuating resource stocks. We examine the degree of substitutability between two key factors - (a) the active promotion of norm adoption by institutions and (b) the impact of social recognition on the opinion formation of peers - for upholding norms and thus securing the CPR. Moreover, we find that while larger sanctions for norm violations and lower material benefits from resource exploitation generally favor resource-conserving behavior in the short run, they may, surprisingly, adversely affect resource conservation in the long run by interfering with cultural dynamics and thereby threatening norm persistence.
Keywords: C73; D02; D62; Q20; Z13; 330